1987
DOI: 10.1007/bf01892354
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between seed size and protein content in newly developed high protein lines of pigeonpea

Abstract: To develop high protein lines, several crosses were made between Cajanus as a source of acceptable seed size and Atylosia as a source of high protein. In the present study, 1974 single F7 plants from these intergeneric crosses were examined. Correlation coefficients among these crosses between seed size and seed protein content ranged from -0.30, (P < 0.01) to +0.28 (P < 0.01). Two crosses had significant negative correlations and one showed a significant positive correlation while in the remaining two no sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
24
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 5 publications
7
24
1
Order By: Relevance
“…This clearly indicated the reverse relationship between protein content and 100 seeds weight. This conclusion was in agreement with that of Saxena et al (1987) on pigeonpea, Kaushik et al (2007) on Jatropha curcas and Afzal et al (2003a, b) on mungbean. It was found that investigated accessions had significant variation in protein content.…”
Section: Discussionsupporting
confidence: 92%
“…This clearly indicated the reverse relationship between protein content and 100 seeds weight. This conclusion was in agreement with that of Saxena et al (1987) on pigeonpea, Kaushik et al (2007) on Jatropha curcas and Afzal et al (2003a, b) on mungbean. It was found that investigated accessions had significant variation in protein content.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, CP content was significantly and negatively correlated (r= −0.17**) with seed weight. In general, associations between CP content and seed weight have been found to be absent or weakly negative in grain legumes [25][26][27][28] and in Cajanus x Atylosia crosses [29]. These results clearly demonstrate that the relationships between seed weight and mineral and CP content vary across species and are mostly nonsignificant in grain legumes.…”
Section: Resultsmentioning
confidence: 61%
“…No interactive effect between the seed mass and the crude protein content could be detected. Saxena et al [17] reported a highly significant negative correlation between seed size and protein content in high-protein lines of pigeon pea. Brunsgaard et al [18], in studies with 31 pea samples, reported that the smaller seeds had significantly higher protein content, but only in comparison with the largest seeds.…”
Section: Resultsmentioning
confidence: 97%